Russian diplomat in Rome: the mission of Prince B. I. Kurakin (1707) - S. S. Kolegov (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The relations between Russia and the papal state in the first years of the Northern war are analyzed. Describes the background to the trip B. I. Kurakin in Rome in 1707, gives a brief overview of the contacts of the Russian state with the States of the Apennine Peninsula at the turn of XVII - XVIII centuries. The personal qualities of the first Russian Ambassador to the court of the Pope are evaluated. Particular attention is paid to the tasks and negotiations held by Kurakin during the execution of his instructions. The description of court ceremonial, diplomatic traditions of Rome is investigated. For a better understanding of the personality, mentality of Kurakin, the article considers the attitude of the Ambassador to the religious holidays of the Catholic state, the everyday life of the population, the ways of spending leisure time by the representatives of the Italian aristocracy. The interest of the Russian diplomat to the historical monuments of Rome, as well as other attractions is noted. The author comes to the conclusion that the trip to the Pope had a contradictory result. Because of the difficult international situation Kurakin failed to achieve support from the Holy see. On the other hand, the information he received enriched domestic diplomacy with valuable experience of relations with a foreign state, and the Russian society with knowledge of traditions and customs of one of the European countries.